Pseudorapidity and transverse-momentum distributions of charged particles in proton-proton collisions at √s=13 TeV - Adam, Jaroslav; Angelov, Venelin; Bock, Friederike; Busch, Oliver; Deisting, Alexander; Fleck, Martin; Glässel, Peter; Karayan, Lilit; Klewin, Sebastian; Knichel, Michael Linus; Leardini, Lucia; Mercado Pérez, Jorge; et al. (Physics letters, 2016)
The pseudorapidity (η) and transverse-momentum (pT) distributions of charged particles produced in proton-proton collisions are measured at the centre-of-mass energy s=13 TeV. The pseudorapidity distribution in |η|<1.8 is reported for inelastic events and for events with at least one charged particle in |η|<1. The pseudorapidity density of charged particles produced in the pseudorapidity region |η|<0.5 is 5.31±0.18 and 6.46±0.19 for the two event classes, respectively. The transverse-momentum distribution of charged particles is measured in the range 0.15<pT<20 GeV/c and |η|<0.8 for events with at least one charged particle in |η|<1. The evolution of the transverse momentum spectra of charged particles is also investigated as a function of event multiplicity. The results are compared with calculations from PYTHIA and EPOS Monte Carlo generators.